Answer: a = 1, b = 0, c = -49
==================================================
Step-by-step explanation:
Expand out the expression using the FOIL rule
(x+7)(x-7)
x^2 - 7x + 7x - 49
1x^2 + 0x - 49
We see that a = 1, b = 0, c = -49
-------------
Another way to expand is to do the following
(x+7)(x-7)
y(x-7) .... let y = x+7
xy - 7y .... distribute
x( y ) - 7( y )
x( x+7 ) - 7( x + 7 ) ... replace y with x+7
x^2 + 7x - 7x - 49 .... distribute
1x^2 + 0x - 49
We get the same result.
-------------
Lastly, a shortcut can be used as yet another method to expand.
The shortcut is the difference of squares rule
(a + b)(a - b) = a^2 - b^2
In this case, a = x and b = 7, so,
(a + b)(a - b) = a^2 - b^2
(x + 7)(x - 7) = x^2 - 7^2
(x + 7)(x - 7) = x^2 - 49
(x + 7)(x - 7) = 1x^2 + 0x - 49